The impact assessment of desalination plant discharges on heavy metal pollution in the coastal sediments of the Persian Gulf - Sharifinia, Moslem; Keshavarzifard, Mehrzad; Hosseinkhezri, Parisa; Khanjani, Mohammad Hossein; Yap, Chee Kong; Smith, Walker O.; Daliri, Moslem; Haghshenas, Arash (Elsevier, 2022)
In recent decades the development of desalination plants (DPs) for desalination of seawater has increased dramatically, while little attention has been paid to the effects of this activity on the accumulation of heavy metals (HMs) in the sediments of affected ecosystems. The present study was implemented to evaluate (1) heavy metal accumulation in sediments impacted by DPs discharges, (2) spatial and temporal changes of HMs and the contamination degree by different types of pollution indexes (single and integrated indices), and (3) ecological risk assessment of cadmium (Cd), lead (Pb), zinc (Zn) and copper (Cu) in sediments affected by DPs discharges. A total of 288 sediment samples were collected seasonally at 24 stations from November 2019 to October 2020. Analysis of HMs concentrations in sediments near the desalination plant discharge provided evidence of local contamination. Maximum concentration of Cu and Pb elements were found in sediments near the desalination plant discharge point. Hierarchical cluster analysis revealed clear segregation of stations impacted by desalination plant discharges and away from discharges. The values of PLI index in sediments of all sampling stations were < 1, indicating that there was no metal pollution by this index. The potential ecological risk index (PERI) ranged from 5.33 ± 0.51 to 11.81 ± 4.98 in sampling sediments and were classified as “low potential ecological risk”. These results demonstrate that the DPs discharge increased HMs concentrations in the sediments in close proximity to outlets. The necessary and practical regulations and policies regarding the rejection of the DPs discharge and disposal of chemical compounds must be implemented and enforced.